Burden of diseases attributed to traffic noise in the metropolis of Tehran in 2017. (15th May 2022) - Shamsipour, Mansour; Zaredar, Narges; Monazzam, Mohammad Reza; Namvar, Zahra; Mohammadpour, Saman
Abstract: Although road traffic noise is the most important source of environmental noise emission in large cities, little is known about health burden. The present study was conducted to estimate the burden of diseases attributed to traffic noise in the metropolis of Tehran in 2017. Using noise maps provided by the municipality of Tehran, we calculated population exposure distribution in term of Ldn and Lnight and the number of DALYs lost due to ischemic heart disease, hypertension, high sleep disturbance, annoyance and stroke endpoints based on the World Health Organization Environmental Noise Guidelines for the European Region. We applied published dose-response functions to estimate the traffic noise burden for high sleep disturbance and annoyance. We estimated 61, 284 DALYs or 697 DALYs per 100, 000 population attributed to traffic noise in Tehran for the reference year 2017. Highly sleep disturbance with a share of 58.74% of the DALYs was recognized as the most important contributor of disease burden, and noise annoyance with a share of 23.12% was ranked next. Ischemic heart disease (11.71%), stroke (5.12%), and hypertension (1.31%) were ranked third to fourth, respectively, in terms of the burden of disease caused by environmental noise. A considerable fraction of the population of Tehran lives in areas with an environmental noise higher than the standard level. The findings showed that traffic noise pollution is an important environmental risk factor in Tehran imposes the greatest burden on the community, mainly through highly sleep disturbance and noise annoyance endpoints. Graphical abstract: Image 1 Highlights: Estimate the exposure to traffic noise in the Tehran in 2017. Estimate the burden of diseases attributed to traffic noise. Only in 2017, about 61, 284 DALYs attributed to traffic noise in Tehran. Highly sleep disturbance is the most important contributor of disease burden.